Pelatihan Pengembangan Instrumen Penilaian Hasil Belajar Pada Guru Tingkat Dasar Di Mi Raudlatul Mubtadiin Kecamatan Ketapang Kabupaten Sampang - Syaiful Rohman (STIT Al - Ibrohimy Bangkalan, 2025)
Assessment is one of the main components in the learning process. The purpose of the assessment includes knowing the level of achievement of learning objectives and seeing the effectiveness of the teaching and learning process. In the assessment of learning outcomes, teachers have a central role as the main supporter to implement an ideal assessment system. Training on the Development of Learning Outcome Assessment Instruments for Elementary School Teachers is very important for us to do, because this can improve the ability and creativity of teachers in making good learning outcome assessment instruments. The results of this activity are that teachers in this school still need further activities or mentoring to get used to developing learning outcome assessment instruments. This activity is very useful, especially for institutions. In addition to increasing knowledge, it will also refresh the knowledge of teachers about the development of assessment instruments. In terms of management, the implementation of this activity will further improve educational services to students and also improve quality.